2019
DOI: 10.1111/1747-0080.12551
|View full text |Cite
|
Sign up to set email alerts
|

Sarcopenia, nutritional status and type 2 diabetes mellitus: A cross‐sectional study in a group of Mexican women residing in a nursing home

Abstract: Aim To evaluate the prevalence of sarcopenia and its association with nutritional status and type 2 diabetes mellitus (T2DM) in older women living in a nursing home. Methods This cross‐sectional study assessed nutritional status using the Mini Nutritional Assessment (MNA). Sarcopenia was defined according to the European Working Group on Sarcopenia in Older People; hand grip strength and physical performance were determined by dynamometry and gait speed, respectively. Muscle mass was assessed using calf circum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
41
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(45 citation statements)
references
References 28 publications
(36 reference statements)
3
41
0
1
Order By: Relevance
“…However, poor nutritional status is not only associated with depression or polypharmacy in older people. Previously published studies showed a strong association between physical dependency and poor nutritional status in Mexican nursing home residents [4]. In a cross-sectional study in community-dwelling older Chinese adults, it was found that complete physical functional dependence was strongly associated with malnutrition [39].…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…However, poor nutritional status is not only associated with depression or polypharmacy in older people. Previously published studies showed a strong association between physical dependency and poor nutritional status in Mexican nursing home residents [4]. In a cross-sectional study in community-dwelling older Chinese adults, it was found that complete physical functional dependence was strongly associated with malnutrition [39].…”
Section: Discussionmentioning
confidence: 93%
“…A recent meta-analysis study including cross-sectional, prospective, retrospective, and case-control studies showed that the prevalence of malnutrition is quite different in older adults living in the community (4.0%) compared to those who are hospitalized (22.3%), those who are living in nursing homes (15.2%), or those in long-term care institutions (30.0%) [ 3 ]. In this regard, very little information is available about the malnutrition prevalence in older Mexican persons, either community-dwelling or living in nursing homes [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…The risk factors related to sarcopenia in elderly people with T2DM are age, diabetes duration, gender, presence of comorbidity, microvascular complications [32,99], reduced hip circumference, lower BMI, low physical activities [100], and poor nutritional status [101,102].…”
Section: Type 2 Diabetes Mellitus and Sarcopeniamentioning
confidence: 99%
“…A large portion of vitamin D requirements is obtained through sunlight exposure in young people; but the supply of this vitamin is reduced in the old age due to an inadequate nutrition and the presence of chronic diseases [24,25]. A poor nutritional status is a frequent health problem found in older adults, and in some populations, it has been found in association with sarcopenia and dynapenia [26][27][28]. Furthermore, it is well known that an inadequate diet is a determinant factor in vitamin D deficiency [29].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, a dramatic worldwide increase in the prevalence of T2DM has been observed in association with skeletal muscle disorders in older adults [41,42]. In this regard, epidemiological studies have shown a high prevalence of sarcopenia in older adults presenting poor nutritional status and T2DM [27,43,44].…”
Section: Introductionmentioning
confidence: 99%